From Promoting Harmony to Spreading Threats: the Languages of Digital Security of Indonesian Cyber Police to Create Political Stability - Sardini, Nur Hidayat; Wijayanto, Wijayanto; Elsitra, Gita Nindya (Politika: Jurnal Ilmu Politik, 2024)
Recently, the Indonesian police has increased its security activities on social media. Not only taking action against digital crimes, they are also pro-active in monitoring social media by finding a new body namely a virtual police. They conduct socialization on what considered appropriate activities on the twitter. Furthermore, they also implement surveillance to the netizen’s activities on twitter and release early warning to those who are considered as violating the law. In the twitter, this function was conducted using their account namely @siberpolri which means Indonesian cyber police. Based on the digital ethnography on the twitter account of the Indonesian cyber police, this study tries to analyze the language used by the Indonesian police to create digital security. This research found that the Indonesian police use the following languages in their posts: first, promoting social harmony in digital public spaces; second, using jokes to divert the discussion away from the political problems to trivial things; third, encouraging the citizens not to criticize the power holders; fourth, creating a narrative of threats to netizens. This study argues that behind the language used, there is an underlying interest of the Indonesian police to create of political stability very much needed to support economic development. In this regards, the languages of digital security will be understood in the context of the ideology of neo developmentalism which is being carried out by President Joko Widodo. It is the ideology which was once used during the New Order era under authoritarian Suharto.